Penegakan Hukum Pidana Yang Optimal (Perspektif Analisis Ekonomi Atas Hukum) - Mahrus Ali (Fakultas Hukum Universitas Islam Indonesia, 2008)
Basically, economic analysis towards criminal law relates to two points namely, rationality and efficiency. Rationality denotes that a person, in committing a crime always takes the cost and benefit into account. While efficiency means that a crime offender tends to use certain way which is less costly in committing the crime. An optimum criminal law enforcement, therefore, may be achieved through a certain method which takes the following three aspects into account; the benefit which is gained by the criminal offender, the lost which is caused by such crime, and also, the expenditure caused by legal enforcement activities